Entrepreneurship and Family Owned Enterprises Model for Long-Term Growth and Success: The Case of Sinokrot - Sonia Ammar; Jet Mboga (Britain International for Academic Research (BIAR-Publisher), 2021)
This article explores the startup, growth, and success factors of Sinokrot Global Group. Sinokrot, a family-owned enterprise located in the Palestinian West Bank. Sinokrot began as a local confection in the West Bank, focusing on Agro-Industries and Agriculture, which has expanded into the global market. The firm employs permanent and seasonal workers from surrounding fifty villages and cities. It accounts for three thousand five hundred workers in Palestine society and ships to over twenty countries worldwide. Despite political and economic challenges in Palestine and the Middle East, Sinokrot has set modern successful business ventures in the Palestinian and other emerging markets. This case study on Sinokrot, now termed Sinokrot Holdings, examines factors that contributed to the success and survival of Sinokrot. A structured interview method is used to elicit relevant information from top management of Sinokrot on its sustainable growth and entry into global markets. We will discuss implications for entrepreneurs in less developed nations. An entrepreneurship success model for family-owned businesses is proposed.